The Importance of Non-Standard Forms of Work in the Current Economic Context - Stahi, Tatiana; Robea, Mariana (Journal of Danubian Studies and Research, 2023)
Starting from the importance of atypical forms of employment in the current economic context and in the light of international regulations - that of responding to an acute need for flexibility in terms of labor markets - our research comes with the presentation of the importance of well-known atypical forms of work both internationally, European as well as domestically. The contemporary context of individual labor relations is characterized by this evolutionary trend of non-standard or atypical forms of work, also supported by the recent Eurostat statistics from the European level, which show that the percentage of growth in standard, permanent, full-time work, it is overtaken by the percentage increase in non-standard, atypical work, an aspect that marks a fundamental problem and not to be neglected in terms of individual labor relations. In fact, a multitude of factors are involved in this phenomenon of the dispersion of flexible work arrangements. From the great contemporary problems determined by the interaction of economic, political, social, cultural, technological and informational processes to the globalization of society, all have determined a diversification of needs from the perspective of employers and implicitly, the abandonment of the standard model of work performance.